2011
DOI: 10.4236/as.2011.22010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low light intensity on growth and yield of four soybean cultivars during wet and dry seasons of northeast thailand

Abstract: Crop is commonly grown in intercrop combinations of which cereal/legumes are the most widespread in tropical countries. The availability of low light intensity due to shading is the critical factor in determining legume yield in intercropping. The experiment searches of better soybean cultivar for intercropping. A field experiment was conducted at the experimental farm of Khon Kaen University in 2005. The objectives of this study were to determine the influence of light regimes (30% of normal light, 50% of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 13 publications
(28 reference statements)
5
10
2
7
Order By: Relevance
“…Observations on plants under rain-shelter showed that those three agronomic traits were less compared to those observed on field trial (Table 3). These results are in line with research found in Japan (Kurosaki and Yumoto 2003;Kakiuchi and Kobata 2006), and in Thailand (Polthanee et al 2011) that low light intensity led to a reduction in the pod number per plant. Although the number of pods reduced, soybean plant under rain-shelter produced larger seed size than those in the field.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Observations on plants under rain-shelter showed that those three agronomic traits were less compared to those observed on field trial (Table 3). These results are in line with research found in Japan (Kurosaki and Yumoto 2003;Kakiuchi and Kobata 2006), and in Thailand (Polthanee et al 2011) that low light intensity led to a reduction in the pod number per plant. Although the number of pods reduced, soybean plant under rain-shelter produced larger seed size than those in the field.…”
Section: Resultssupporting
confidence: 82%
“…Soybean plant under rain-shelter grew higher than those in the field (Table 3). Polthanee et al (2011) also found the same that differences in the intensity of solar radiation affected soybean stem elongation. Soybean grows in height between 10% and 24% under low light.…”
Section: Resultssupporting
confidence: 54%
“…Berbagai hasil penelitian menunjukkan pengurangan intensitas cahaya matahari pada tumpangsari jagung-kedelai berkisar antara 30-50% cahaya penuh (Polthanee et al 2011, He et al 2012. Pengurangan tersebut berpengaruh negatif terhadap pertumbuhan tanaman (Panhwar et al 2004), berkurangnya luas daun total 28% dari tanpa naungan (Pantilu et al 2012, Muhuria et al 2006, jumlah polong per tanaman (Kakiuchi dan Kobata 2006, Polthanee et al 2011, hasil biji (Zhang et al 2011), bobot 1.000 biji (Liu et al 2010), meningkatkan tinggi tanaman dan mengurangi diameter batang kedelai (Bakhshy et al (2013). Peningkatan tinggi tanaman disebabkan oleh pemanjangan ruas batang (etiolasi) (Li et al 2006, Paciullo et al 2011.…”
Section: Pendahuluanunclassified
“…Secara fisiologis, genotipe yang mampu beradaptasi terhadap intensitas cahaya rendah mempunyai kandungan klorofil b lebih tinggi dibandingkan dengan varietas rentan. Karakter fisiologi ini dapat digunakan sebagai indikator dalam program pemuliaan kedelai toleran naungan (Polthanee et al 2011).…”
Section: Pendahuluanunclassified
“…Jumlah polong isi di Tulangbalak setara dengan naungan buatan 50%, sedangkan di Gunungsari dan Gunungadi setara dengan tumpangsari jagung-kedelai dan ubikayu-kedelai . Menurut Polthanee et al (2011), penurunan jumlah polong dipengaruhi oleh jenis kultivar dan naungan pada musim hujan maupun musim kering. Naungan 30% dan 50% menyebabkan pengurangan jumlah polong masing-masing 32% dan 14% pada musim hujan, 21% dan 17% pada musim kering.…”
Section: Hasil Dan Pembahasanunclassified